A Functional Cognitive Stylistic Study of Online Horoscopes Predictions - Rahma Amer Efleih; Eman Adil Jaafar (مجلة كلية التربية للبنات, 2025)
The present study mainly investigates the linguistic choices used in daily horoscope predictions that attract the attention of readers globally. It employs a functional cognitive stylistic approach to analyze the language of horoscopes, concentrating on how linguistic structures shape meaning and reader interpretation. The primary objectives are to explore how functional cognitive stylistics improves the understanding of language use in horoscopes. The study adopts a qualitative eclectic model that integrates functional cognitive stylistics to achieve these goals. It adopts the tools of functional stylistics, particularly textual metafunctions (Halliday & Matthiessen, 2014), Moreover, it applies Schema Theory to explore how readers' pre-existing knowledge impacts their understanding, and Figure-Ground Theory (Stockwell, 2020) examines the emphasis on specific elements to guide focus while textual metafunctions establish discourse by structuring information flow, enhancing readability, and supporting key ideas within the horoscope predictions. Daily horoscope predictions published on Vogue India's website is the target of the study. The findings show that horoscopes capture attention and support important concepts through vague but captivating language. The language of horoscopes contains crucial cues that activates readers’ schema